Hydrologic assessment of check dam performances in semi-arid areas: a case study from Gujarat, India - Mozzi, G.; Pavelic, Paul; Alam, Mohammad Faiz; Stefan, C.; Villholth, Karen G. (Frontiers Media, 2021)
In semi-arid India, managed aquifer recharge (MAR) is often used to enhance aquifer storage, and by implication, water security, and climate resilience, by capturing surface runoff, mainly through check dams implemented at the community level. Despite their extensive use, the design of these structures typically does not follow a systematic method to maximize performance. To aid in the improvement of check dam design parameters and location siting, we develop a dynamic tool, which integrates the daily water balance of a check dam with analytical infiltration equations to assess check dam performance measured as temporal dynamics of storage, infiltration, and evaporation. The tool is implemented in R environment and requires meteorological and hydrogeological data, as well as check dam geometry and nearby well-abstractions, if any. The tool is applied to a case study in Saurashtra in Gujarat, where field visits were conducted. Simulations show that typical check dams in the area are able to store a volume between three and seven times their storage capacity annually. Infiltration volumes highly depend on hydroclimatic and hydrogeological conditions, as well as the formation of a clogging layer, highlighting the importance of site selection and periodic maintenance. The tool is validated with data from a previous study in Rajasthan, where daily water balance parameters were monitored. Validation results show an average R 2 of 0.93 between the simulated and measured water levels. The results are adequate to suggest that the tool is able to assist in check dam planning in semi-arid environments.